Longitudinal Characterization of Immune Response in a Cohort of Children Hospitalized with Multisystem Inflammatory Syndrome - Laura Dotta; Daniele Moratto; Marco Cattalini; Sara Brambilla; Viviana Giustini; Antonella Meini; Maria Federica Girelli; Manuela Cortesi; Silviana Timpano; Anna Galvagni; Anna Viola; Beatrice Crotti; et al. (MDPI AG, 2023)
Background: Multisystem Inflammatory Syndrome in Children (MIS-C) is a severe complication of SARS-CoV-2 infection caused by hyperactivation of the immune system. Methods: this is a retrospective analysis of clinical data, biochemical parameters, and immune cell subsets in 40 MIS-C patients from hospital admission to outpatient long-term follow-up. Results: MIS-C patients had elevated inflammatory markers, associated with T- and NK-cell lymphopenia, a profound depletion of dendritic cells, and altered monocyte phenotype at disease onset, while the subacute phase of the disease was characterized by a significant increase in T- and B-cell counts and a rapid decline in activated T cells and terminally differentiated B cells. Most of the immunological parameters returned to values close to the normal range during the remission phase (20-60 days after hospital admission). Nevertheless, we observed a significantly reduced ratio between recently generated and more differentiated CD8+ T- and B-cell subsets, which partially settled at longer-term follow-up determinations. Conclusions: The characterization of lymphocyte distribution in different phases of MIS-C may help to understand the course of diseases that are associated with dysregulated immune responses and to calibrate prompt and targeted treatments.